Актуальність управлінського обліку на сучасних підприємствах - Безверхня, Юлія Вікторівна; Безверхняя, Юлия Викторовна; Bezverkhnya, Yuliia (My University, 2019)
UK: У статті розглянуті ключові поняття та тенденції розвитку управлінського обліку у сучасних умовах господарювання. Проаналізовані проблеми побудови єдиного облікового інформаційного простору підприємства. Досліджено забезпечення інформаційної підтримки користувачів у процесі ухвалення управлінських рішень. Визначена ефективність використання комунікаційної системи управлінського обліку під час створення інтегрованої автоматизованої системи стратегічного планування та бухгалтерського обліку. Обґрунтована побудова системи управлінського обліку, яка забезпечує високий рівень ефективності виробництва та його конкурентоспроможності. Встановлено, що для розвитку економічного потенціалу підприємства необхідний управлінський облік за центрами відповідальності та стратегічне управління витратами. RU: В статье рассмотрены ключевые понятия и тенденции развития управленческого учета в современных условиях хозяйствования. Проанализированы проблемы построения единого учетного информационного пространства предприятия. Исследовано обеспечение информационной поддержки пользователей в процессе принятия управленческих решений. Определена эффективность использования коммуникационной системы управленческого учета при создании интегрированной автоматизированной системы планирования и бухгалтерского учета. Обосновано построение системы управленческого учета, которая обеспечивает высокий уровень эффективности производства и его конкурентоспособности. Установлено, что для развития экономического потенциала предприятия необходим управленческий учет по центрам ответственности и стратегическое управление затратами. EN: This study is devoted to the problem of relevance of the management accounting system in modern Ukrainian enterprises. In the modern economy, the principles of the relationship between management accounting and strategic goals of the enterprise require clarification and theoretical understanding. Practice shows that competent and scientifically based construction of the management accounting system provides a high level of production efficiency and competitiveness. The article deals with the key concepts and trends in the development of management accounting in modern economic conditions. Management accounting, as a relatively self-existing set of elements and links between them, should function and be regulated on the basis of internal and General regulatory framework. The problems of building a single accounting information space of the enterprise are analyzed. Any enterprise should decide for itself the question of the degree of openness of information; risks associated with openness; take measures to improve the reliability of reporting data; think about how users will perceive the information provided; ensure effective exchange of information between its units. The provision of information support to users in the process of managerial decision-making is investigated. The concept of accounting information space assumes creation of conditions for providing with accounting data of all users in constantly changing economic situation. Efficiency of use of communication system of management accounting at creation of the integrated automated system of planning and accounting is defined. The author substantiates the construction of a management accounting system that provides a high level of production efficiency and competitiveness. Enterprise management functions can be divided into two main blocks: which provide efficiency and which provide reliability. It is established that for the development of the economic potential of the enterprise, management accounting for responsibility centers and strategic cost management is necessary. It is concluded that the objectives of the strategy of formation and development of the economic mechanism of management fully coincide with the priority goals of modern enterprise development and are designed to ensure their implementation by building an adequate system of management accounting, including management of responsibility centers and strategic cost management.
Relevance of management accounting in modern enterprises
Keywords: управлінський облік; інформація; підприємство; управління; витрати; центри відповідальності; управленческий учет; информация; предприятие; управление; затраты; центры ответственности; management accounting; information; enterprise; management; expenses; responsibility centers